PENGARUH PELATIHAN PLYOMETRICS ZIG-ZAG DRILLS TERHADAP DAYA LEDAK DAN KEKUATAN OTOT TUNGKAI PADA SISWA PUTRA KELAS VIII SMP N 1 MENGWI TAHUN PELAJARAN 2012/2013 - Krismana Putra, I Nyoman (Universitas Pendidikan Ganesha, 2013)
This study aims to prove the influence of training plyometrics zig-zag drills against yield and strength of limb muscles. This type of research is a true experiment with the design of the study randomized pre-test post-test control group design. Samples of the student’s research is the son of class VIII SMP N 1 Mengwi year 2012/2013 lessons as much as 40 people then divided into two groups. An explosive vertical jump test measured by muscle power while limbs are measured with a leg dynamometer, the next leg of the test data were analysed by t-test for independent significance level 0,05 at with the help of the program SPSS 16,0. Based on the results of the analysis of research data, using independent t-test for the data yield limb muscles gained significance rating count is smaller than the value of a (sig < 0,05) which is equal to 0,001. As for limb muscle strength data obtained significance value count is smaller than the value of a (sig < 0,05) which of research plyometrics zig-zag drills training effect on yield and strength of limb muscles is acceptable. Recommended for sports players (teachers, coaches, builders of the sports and athletes) by using the plyometrics zig-zag drills training as one alternative in increasing yield and strength of limb muscles.